Phenotypic Heterogeneity in Attachment of Marine Bacteria toward Antifouling Copolymers Unraveled by AFM - El-Kirat-Chatel, Sofiane; Puymege, Aurore; Duong, The H.; Van Overtvelt, Perrine; Bressy, Christine; Belec, Lénaïk; Dufrêne, Yves F.; Molmeret, Maëlle (Frontiers in Microbiology, 2017)
Up to recent years, bacterial adhesion has mostly been evaluated at the population level. Single cell level has improved in the past few years allowing a better comprehension of the implication of individual behaviors as compared to the one of a whole community. A new approach using atomic force microscopy (AFM) to measure adhesion forces between a live bacterium attached via a silica microbead to the AFM tipless cantilever and the surface has been recently developed. The objectives of this study is to examine the bacterial adhesion to a surface dedicated to ship hulls at the population and the cellular level to understand to what extent these 2 levels could be correlated. Adhesion of marine bacteria on inert surfaces are poorly studied in particular when substrata are dedicated to ship hulls. Studying these interactions in this context are worthwhile as they may involve different adhesion behaviors, taking place in salty conditions, using different surfaces than the ones usually utilized in the literacy. FRC (fouling release coatings)–SPC (self-polishing coatings) hybrids antifouling coatings have been used as substrata and are of particular interest for designing environmentally-friendly surfaces, combining progressive surface erosion and low adhesion properties. In this study, a hybrid coating has been synthetized and used to study the adhesion of three marine bacteria, displaying different surface characteristics, using microplate assays associated with confocal scanning laser microscopy (CSLM) and AFM. This study shows that the bacterial strain that appeared to have the weakest adhesion and biofilm formation abilities when evaluated at the population level using microplates assays and CSLM, displayed stronger adhesion forces on the same surfaces at the single cell level using AFM. In addition, one of the strains tested which presented a strong ability to adhere and to form biofilm at the population level, displayed a heterogeneous phenotypic behaviour at the single cell level. Therefore, these results suggest that the evaluation of adhesion at the population level cannot always be correlated with adhesion forces measured individually by AFM and that some bacteria are prone to phenotypic heterogeneity among their population.